PLANNING FOR THE SOCIALLY MARGINALIZED GROUPS - State Planning Board, Government of Kerala
Although the growth process in Kerala has been more inclusive than in other states of India, there are historical inequalities that have persisted over time and remain a potential source of conflict within the state. The state develops a strategy for the socially marginalised groups. It proposes a different strategy for SCs and ST. While SCs should be brought into the mainstream, STs, culture needs to be celebrated. However, the SC and STs need targeted interventions in education and health to lessen historic inequities.